Pengaruh Penggunaan E-Commerce, Financial Technology dan Media Sosial Terhadap Peningkatan Pendapatan UMKM Kota Dumai - Agnesia, Vionna; Saputra, Agung Joni (E-Jurnal Akuntansi; Vol 32 No 3 (2022)DO - 10.24843/EJA.2022.v32.i03.p15, 2022)
This study aims to show how much influence the use of e-commerce technology, financial technology and social media has on increasing the income of MSMEs in Dumai City. This research uses probability sampling method with simple random sampling technique. The population in this study is the owner of MSMEs in Dumai City. The data analysis technique in this study used multiple linear regression analysis. The results of the study prove that the use of e-commerce and financial technology has no effect on increasing MSME income. Meanwhile, social media has a positive effect on increasing the income of MSMEs in Dumai City. However, the use of e-commerce, fintech and social media has a simultaneous effect on increasing the income of MSMEs in Dumai City. This proves the importance of knowledge and education about the use of technology in running a business to gain greater profits than before. Keywords: E-Commerce; Financial Technology; MSME Income; Social Media.